Analisis kemiripan komunitas artropoda predator hama padi penghuni permukaan tanah sawah rawa lebak dengan lahan pinggir di sekitarnya - Effendy Effendy; Usna Hety; Siti Herlind; Chandra Irsan; Rosdah Thalib (Jurnal Entomologi Indonesia, 2013)
There are approximately 1.4 million hectares of swampy area in South Sumatera, but only 12% of those are being used as farm and plantation.   The purpose of this research was to investigate the similarity of arthropod community inhabiting swampy rice field and its surrounding area. This research was conducted in South Sumatera Province covering regency of Musi Banyuasin and Palembang. Four types of swampy area were selected from each location, i.e. rice field, thicket, bush, and swampy land inhabited by broad-leaf weeds. Pitfall trap used to collect arthropod and it installed at five different times. i.e. 15 days before rice planting, one month, two months, and three months after planting, and 15 days after harvest time. The result showed that relative abundance of predatory arthropod dwelling soil in rice field was 95.03%, and habitat surrounding rice field was 95.12–97.21%. The level of similarity of arthropod species between rice field ecosystem and its surrounding area ranged from 0.73 to 0.84.   Thus, the surrounding area of rice field probably can be used as catchment area of predatory arthropod and other pests during planting season.